Weierstrass transformation in algebra of mnemofunctions - Romashevsky, Alexey B. (Mathematical Modelling and Analysis, 1997)
“Weierstrass transformation in algebra of mnemofunctions” Mathematical Modelling Analysis, 2(1), p. 138-142. First Published Online: 14 Oct 2010